State Price Regulation and Competition Support in the Crisis Period: Sociological Aspects - Maria S. Baynova (Вестник Кемеровского государственного университета. Серия: политические, социологические и экономические науки)
The topic of the article is relevant due to the development of state price regulation during the crisis. Measures to curb price growth provoke discussion about the role of state regulation in the economy, the importance of competition for price reduction, and the essence of market economy. The purpose is to summarize the opinions of entrepreneurs about directions of price growth regulation in Russia. The objectives are to combine sociological data and expert’s opinions regarding government price regulation measures, analyze the results of the author’s survey of entrepreneurs, evaluate the results based on the review of scientific literature on the Russian competitive environment. The authors analyzed the results of sociological surveys and expert discussions, presented the results of author's survey. Entrepreneurs are ready to accept state price regulation due to high monopolization in the fuel and energy sector, agriculture, and retail trade. Entrepreneurs are also interested in reducing the tax burden and loan rates.